DIAGNOSIS OF "MENTAL BURNOUT" OF ANESTHESIOLOGISTS AND REANIMATOLOGISTS - Bakhtigul D. Yusupova; Shirina A.Valijonova; Azizbek F.Valijonov (Scholar Express Journals, 2023)
Currently, special attention is drawn to the problem of the influence of professional activity on the psycho-emotional state of those specialists whose work is associated with intense and intense interaction with people. These specialists have certain mental and physiological reactions, which are considered as a manifestation of professional stress. With good reason, anesthesiologists-resuscitators can be attributed to the category of persons most susceptible to professional stress. In recent years, there has been a significant increase in the functional load of these specialists, which is associated with an increase in surgical activity, an increase in the number of operated patients with severe concomitant pathology and naturally leads to a high level of mental tension. These include factors of a socio-psychological nature - the processes of interaction in the system "anesthesiologist - surgeon - patient", as well as group processes in the anesthesiology team itself.
Keywords: mental burnout; depersonalization; maladjustment